2017
DOI: 10.37358/rc.17.11.5913
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Content and Dynamics of Nutrients in Water and Sediments from the Plumbuita Lake, Bucharest. I. Study on Phosphorous Content and Distribution

Abstract: Nutrient pollution of surface waters is a challenge of the modern society, leading to the occurrence of the eutrophication phenomenon which limits the uses of the aquatic resources for various purposes. The aim of this study was the evaluation of water and sediment status of the Plumbuita Lake (Bucharest-Romania), focusing on phosphorous speciation (phosphorous bonded to iron and aluminium, phosphorous bonded to calcium, and soluble and loosely sorbed phosphorous bonded to carbonate) and dynamics as this eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It was also found that organic nitrogen accounts for 99% of the total nitrogen, while ammonia was best represented among ionic nitrate species, followed by nitrates and nitrites. The results of the water quality indicators reported were pH levels from 7.5 to 9.43, TP values between 0.07 and 0.46 mg/L, DO values from 7.58 to 9.43 mg/L, BOD values from 3.39 to 8.73 mg/L, and TN values ranging from 1.52 to 3.79 mg/L [56,57]. Stefan et al also investigated the trophic stage of Snagov Lake, using data collected between April 2010 and October 2014 [58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that organic nitrogen accounts for 99% of the total nitrogen, while ammonia was best represented among ionic nitrate species, followed by nitrates and nitrites. The results of the water quality indicators reported were pH levels from 7.5 to 9.43, TP values between 0.07 and 0.46 mg/L, DO values from 7.58 to 9.43 mg/L, BOD values from 3.39 to 8.73 mg/L, and TN values ranging from 1.52 to 3.79 mg/L [56,57]. Stefan et al also investigated the trophic stage of Snagov Lake, using data collected between April 2010 and October 2014 [58].…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of water quality of the four small artificial lakes in the Bucharest-Ilfov metropolitan area is based on the determination of ecological status by assessing chemical and physicochemical characteristics. y n n [56] Bucharest 2…”
Section: Measurements ** Namementioning
confidence: 99%
“…According to the OECD (World Economic Cooperation and Development Organization), 80% of water eutrophication has been attributed to phosphorus, 10% of water bodies eutrophication directly related to nitrogen and phosphorus and the remaining 10% has been triggered by nitrogen and other factors [14]. The effects of eutrophication are numerous including, inter alia, the excessive growth of algae, the increase in the production of organic matter, which leads to the generation of hypoxic/anoxic conditions [15]. The chemical, biological and physical treatments have been very diverse based on the local regulations and level of pollutants [16].Unfortunately, most of the pollutants have a longer life time, they are resilient into the nature and could spread over large areas and they could accumulate into aquatic organisms.…”
mentioning
confidence: 99%
“…Nowadays, the protection of aquatic life and human life is a permanent concern, so monitoring the quality of surface water has an important role to play [9,10]. According to studies in the field, the presence of chemical pollutants in the environment, especially from anthropogenic sources, represents a threat to living organisms [11][12][13]. Pollutants and potentially toxic elements (like heavy metals) can accumulate in quantities exceeding the maximum admissible limits in both surface and underground waters and soil.…”
mentioning
confidence: 99%